Advanced Therapeutic Applications of Algae in Combatting Infectious Diseases: Antimicrobial, Immunomodulatory, and Anti-inflammatory Approaches - Sunil N. Thitame; Ashwini A. Aher (Journal of Pharmacy and Bioallied Sciences)
Algae are photosynthetic organisms belonging to diverse groups, which have received much interest recently due to their anti-infective properties. These organisms synthesize bioactive compounds that exhibit considerable antimicrobial, immunomodulatory, and anti-inflammatory activities. In this paper, we review evidence on the potential of algae in modifying infectious pathogens, with particular emphasis on the antimicrobial ability of algae against bacteria, fungi, and viruses, as well as their ability to regulate immune responses and inflammation. Algae with conventional antibiotics may be useful for proposing a new strategy for combatting infectious diseases.